2009
DOI: 10.1002/pmic.200800713
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic‐based approach for the identification of immunodominant Cryptococcus neoformans proteins

Abstract: Cryptococcus neoformans is an opportunistic fungal pathogen that can cause life-threatening meningoencephalitis in immune compromised patients. Previous, studies in our laboratory have shown that prior exposure to an IFN-γ-producing C. neoformans strain (H99γ) elicits protective immunity against a second pulmonary C. neoformans challenge. Here, we characterized the antibody response produced in mice protected against experimental pulmonary C. neoformans infection compared to non-protected mice. Moreover, we ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
71
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 80 publications
6
71
1
Order By: Relevance
“…23,29 To verify a reduction in fungal load and to assess macrophage recruitment during C. neoformans strain H99␥ infection, BALB/c mice were given an intranasal inoculation with 1 ϫ 10 4 CFU of either C. neoformans strain H99␥ or wild-type C. neoformans strain H99, and the pulmonary fungal burden was quantified on days 3, 7, and 14 postinoculation. Figure 1A demonstrates that pulmonary fungal burden was significantly decreased on day 14 postinoculation in mice given an experimental pulmonary infection with C. neoformans strain H99␥ compared with wild-type infected mice (P Ͻ 0.01).…”
Section: Effect Of Ifn-␥ Transgene Expression By C Neoformans Strainmentioning
confidence: 99%
“…23,29 To verify a reduction in fungal load and to assess macrophage recruitment during C. neoformans strain H99␥ infection, BALB/c mice were given an intranasal inoculation with 1 ϫ 10 4 CFU of either C. neoformans strain H99␥ or wild-type C. neoformans strain H99, and the pulmonary fungal burden was quantified on days 3, 7, and 14 postinoculation. Figure 1A demonstrates that pulmonary fungal burden was significantly decreased on day 14 postinoculation in mice given an experimental pulmonary infection with C. neoformans strain H99␥ compared with wild-type infected mice (P Ͻ 0.01).…”
Section: Effect Of Ifn-␥ Transgene Expression By C Neoformans Strainmentioning
confidence: 99%
“…Previous studies demonstrated that experimental pulmonary infection with a C. neoformans strain engineered to express IFN-␥, strain H99␥, results in the generation of a polarized Th1-type cytokine response in mice (36). Mice given a pulmonary infection with C. neoformans strain H99␥ resolve the acute infection and are completely protected from a secondary infection with wild-type (WT) cryptococci (36,38,40). Recently, we demonstrated that clearance of infection with C. neoformans strain H99␥ is associated with the induction of inducible nitric oxide synthase (iNOS) expression, caMac, and pulmonary Th1-type cytokine production (15).…”
mentioning
confidence: 99%
“…In addition to the results seen with enolase and GAPDH described above, the C. gattii VGIIb strain secreted glucose-6-phosphate isomerase, which has been linked to the development of rheumatoid arthritis following Aspergillus infection (56). Further, some non-classically secreted proteins identified in this study, including fungal serinetype endopeptidases (57) and transaldolase, an immunodominant protein in C. neoformans (58)(59)(60), have been found to bind IgE. The presence of immunogenic proteins in the VGIIb secretome might be expected to provoke rapid induction of the innate immune response, preventing the initiation of disease.…”
Section: Discussionmentioning
confidence: 88%